2021
DOI: 10.1111/cobi.13686
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term drivers of persistence and colonization dynamics in spatially structured amphibian populations

Abstract: Many organisms live in networks of local populations connected by dispersing individuals, called spatially structured populations (SSPs), where the long-term persistence of the entire network is determined by the balance between two processes acting at the scale of local populations: extinction and colonization. When multiple threats act on an SSP, a comparison of the different factors determining local extinctions and colonizations is essential to plan sound conservation actions. Here we assessed the drivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 48 publications
(101 reference statements)
2
39
0
Order By: Relevance
“…The crayfish showed its stronger effects at the SSP scale (Figure 3c), in agreement with previous studies on amphibian population dynamics (Falaschi et al, 2021; Manenti et al, 2020). The strong relationship between crayfish incidence and abundance confirms that this invasive species can alter SSP dynamics across the landscape and possibly reduce the number of immigrants from nearby wetlands (Manenti et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The crayfish showed its stronger effects at the SSP scale (Figure 3c), in agreement with previous studies on amphibian population dynamics (Falaschi et al, 2021; Manenti et al, 2020). The strong relationship between crayfish incidence and abundance confirms that this invasive species can alter SSP dynamics across the landscape and possibly reduce the number of immigrants from nearby wetlands (Manenti et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The red swamp crayfish has a great potential to negatively affect frog populations: it has a generalist diet, can feed on tadpoles and egg masses, and can modify habitats through the consumption of macrophytes and burrowing (Cruz et al, 2006;Lo Parrino et al, 2020). Previous analyses on the presence/absence of R. dalmatina revealed no site-level effect of invasive crayfish (Bélouard et al, 2019;Falaschi et al, 2021). Still, our results indicate lower abundance in wetlands occupied by this invasive species (Figure 3c), even if the crayfish was only found in a few sites (max.…”
Section: Effect Of Variables On Abundancementioning
confidence: 99%
“…Few studies have investigated behavioral responses of amphibian larvae to this invasive crayfish, and to our knowledge only one of them showed that behavioral shifts can improve the survival of larvae (Polo-Cavia and Gomez-Mestre 2014), while others suggested that reduction of activity and/or altered microhabitat use do not necessarily reduce vulnerability (Rebelo and Cruz 2005). In fact, multiple native amphibians underwent rapid declines and local extinctions after the invasion of the American crayfish (Gamradt and Kats 1996, Cruz et al 2008, Ficetola et al 2011, Liu et al 2018, Falaschi et al 2021, suggesting that the responses of native amphibians can be insufficient to withstand the predatory pressure posed by this voracious crayfish, at least for some species.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays Procambarus clarkii is widespread in Italy and it invaded the study area between (Lo Parrino et al 2020). Landscape-level analyses have shown that the crayfish has strong effects on frog populations, reducing tadpole survival in the wild and affecting the dynamics of population networks (Ficetola et al 2012, Falaschi et al 2021.…”
Section: Study Systemmentioning
confidence: 99%
“…Despite the strong predatory pressure imposed by Procambarus clarkii, so far, the total abundance of clutches in invaded populations by the crayfish does not seem to have undergone a significant decrease (Manenti et al 2020). Frog persistence is certainly due to the immigration of frog individuals from source populations , Falaschi et al 2021), but it is also possible that plastic and adaptive responses to this predator help to counteract the heavy predator pressure, allowing a sufficient number of tadpoles to attain metamorphosis.…”
Section: Aicmentioning
confidence: 99%